Effect of in-season creatine supplementation on body composition and performance in rugby union football players - Chilibeck, P. D.; Magnus, C.; Anderson, M. (Applied Physiology, Nutrition, and Metabolism, 2007)
Rugby union football requires muscular strength and endurance, as well as aerobic endurance. Creatine supplementation may enhance muscular performance, but it is unclear if it would interfere with aerobic endurance during running because of increased body mass. The purpose of this study was to determine if creatine supplementation during 8 weeks of a season of rugby union football can increase muscular performance, without negatively affecting aerobic endurance. Rugby union football players were randomized to receive 0.1 g·kg-1·d-1 creatine monohydrate (n = 9) or placebo (n = 9) during 8 weeks of the rugby season. Players practiced twice per week for approximately 2 h per session and played one 80 min game per week. Before and after the 8 weeks, players were measured for body composition (air displacement plethysmography), muscular endurance (number of repetitions at 75% of one repetition maximum (1 RM) for bench press and leg press), and aerobic endurance (Leger shuttle-run test with 1 min stages of progressively increasing speed). There were time main effects for body mass (-0.7 ± 0.4 kg; p = 0.05), fat mass (-1.9 ± 0.8 kg; p < 0.05), and a trend for an increase in lean tissue mass (+1.2 ± 0.5 kg; p = 0.07), with no differences between groups. The group receiving creatine supplementation had a greater increase in the number of repetitions for combined bench press and leg press tests compared with the placebo group (+5.8 ± 1.4 vs. +0.9 ± 2.0 repetitions; p < 0.05). There were no changes in either group for aerobic endurance. Creatine supplementation during a rugby union football season is effective for increasing muscular endurance, but has no effect on body composition or aerobic endurance.